Religious Activities of The Scavenger at The Landfill in West Java Region - Hanny Hafiar; Priyo Subekti; Aat Ruchiat Nugraha (Karsa: Journal of Social and Islamic Culture, 2019)
Scavenger is a profession that is identical to the waste. Waste has the impression of dirty and contain unclean elements in it that far from the impression well worth to clean concept juxtaposed with the concept of clean and holy. Whereas every Muslim is required to be free from both large and small hadats and in the state of purification when conducting religious activities, must purify themselves, their clothes, or the place to be used to pray. The scavenger who becomes the respondents was the muslims scavengers which would require to run the order to conduct worship, one of them worship rituals that sharia compliant. This study  was conducted to explain the perception and behavior of scavengers at the landfill in religious activity, in connection with the work which is not far from the dirty waste. The method is performed in a descriptive way, with data collected using the open questionnaire, interviews, and observation. The results obtained indicate that: there are scavengers who participate in religious activities held around their neighborhood temporarily domiciled, with motives to stay in touch, gain knowledge, seek peace of mind, and gain merit from God. While the obstacles faced by scavengers to participate in these activities revolve around the limitations of time, psychologically feel they do not have the supporting facilities and equipment for these activities, as well as the stereotypes of a small number of individuals in the surrounding environment to their existence in these activities.